族群及其他考量 ：新加坡华人在马国新山购屋攻略 = Ethnic and other considerations : Singaporean buying houses in Iskandar Malaysia - 郑志祥 Tay, Zhi Xiang (2015)
殖民地时代的新加坡，种族分区而生活。新加坡独立后推行一系列的种族和谐政策，其一便是1989年实施的房屋种族比例政策。经过30余年，新加坡人是否依然存在种族意识，非常值得研究。近年，新加坡人跨国到不受种族政策限制的柔佛依斯干达发展区购屋。大多数接受调查的人，在有选择的情况下，都会倾向于跟自己一样族群的人为邻，部分的人甚至带有国族意识，同时也关注投资回报率和安全。这一系列调查反映出房屋种族比例政策只在国内达到一定的效果，没有在跨国范围内发挥约束力。 During the colonial era, the different races in Singapore lived separately; interaction between different ethnic groups was minimal. Upon achieving independence, Singapore implemented a series of racial-related policies, aiming to achieve racial harmony. The Ethnic Integration policy (EIP) is one of the important racial policies that was implemented 30 years ago. Thus, it is worthwhile for us to investigate whether racial consciousness still exists in Singaporeans today. In recent years, a large number of Singaporeans have been making transnational property purchases over at Iskandar Malaysia. Unlike Singapore, Iskandar Malaysia does not have any EIP-related Policy. Singaporeans are able to choose their neighbours, in particular the ethnic group that their neighbours belong to. Singaporeans who participated in the survey and interviews show that if they are given the chance to choose their neighbours, they will choose to have neighbours of their own ethnic group. This research also shows that Singaporeans have racial consciousness and even nation consciousness. Thus, the strong effect of EIP can only be maintained within Singapore and not transnationally. The main concern that Singaporean buyers have over buying property in Iskandar Malaysia is mainly investment returns and a safe environment.